Exploring the relation between people’s theories of intelligence and beliefs about brain development - Thomas, Ashley J.; Sarnecka, Barbara W. (Frontiers in Psychology, 2015)
A person’s belief about whether intelligence can change (called their implicit theory of intelligence) predicts something about that person’s thinking and behavior. People who believe intelligence is fixed (called entity theorists) attribute failure to traits (i.e. “I failed the test because I’m not smart.”) and tend to be less motivated in school; those who believe intelligence is malleable (called incremental theorists) tend to attribute failure to behavior (i.e. “I failed the test because I didn’t study.”) and are more motivated in school. In previous studies, researchers have characterized participants as either entity or incremental theorists based on their agreement or disagreement with three statements. The present study further explored the theories-of-intelligence construct in two ways: first, we asked whether these theories are coherent, in the sense that they show up not only in participants’ responses to the three standard assessment items, but on a broad range of questions about intelligence and the brain. Second, we asked whether these theories are discrete or continuous. In other words, we asked whether people one thing or the other (i.e. that intelligence is malleable or fixed), or if there is a continuous range of beliefs (i.e., people believe in malleability to a greater or lesser degree). Study (1) asked participants a range of general questions about the malleability of intelligence and the brain. Study (2) asked participants more specific questions about the brains of a pair of identical twins who were separated at birth. Results showed that theories of intelligence are coherent: participants’ responses to the three standard survey items are correlated with their responses to questions about the brain. But the theories are not discrete: although responses to the three standard survey items fell into a bimodal distribution, responses to the broader range of questions fell into a normal distribution suggesting the theories are continuous.